Behavioral risk factors and maternal nutrition as predictors of pre-eclampsia among pregnant women in rural areas: cross-sectional study - Azza, Awatiful; Esti Yunitasari; Mira Triharini; Susilo, Cipto (Universitas Airlangga, 2023)
Introduction: The behavior of pregnant women in caring for pregnancy is influenced by the environment, culture, and lifestyle of the community. This study aimed to analyze the behavior of pregnant women and their nutritional status during pregnancy contributes to the incidence of pre-eclampsia in rural areas. Methods: This study used a cross-sectional approach to 210 pregnant women who visited a community health center in East Java, Indonesia, in the period June 2020-February 2022. Potential risk factors, including maternal behavior in care during pregnancy, and obesity were evaluated as determinants of pre-eclampsia and its subtypes. The assessment instrument uses a structured questionnaire and has been tested for validity and reliability. Logistic regression analysis was used to determine potential risk factors. Odds ratios with 95% confidence intervals (CI) were calculated to estimate the effects of individual factors. All statistical analyses were performed with SPSS version 22.0 with a p-value < 0.05 considered significant. Results: There were 65 (31%) pregnant women experiencing pre-eclampsia from 210 samples. Maternal behavior during pregnancy could predict the incidence of pre-eclampsia (p = 0.001; 95% CI 0.121-0.583; OR = 0.266) while obesity was able to predict pre-eclampsia (p = 0.00; 95% CI 1.705-5.209; OR = 3.00). the age of pregnant women p = 0.014; 95% CI 1.143-3,355; OR = 1.959), and history of hypertension p = 0.036; 95% CI 1.053 – 4.550; OR = 2.189). Conclusions: The behavior and nutritional status of pregnant women have been proven to influence the incidence of pre-eclampsia.